The effect of political uncertainty on the cost of corporate debt - Waisman, Maya; Ye, Pengfei; Zhu, Yun (Journal of Financial Stability, 2015)
In this paper we bring new empirical evidence that political uncertainty is associated with higher corporate debt financing costs. Controlling for all bond and firm characteristics that could affect a firm's cost of debt financing, the uncertainty associated with the outcome of U.S. presidential elections leads to a 34 basis point increase in corporate bond spreads, with closer campaign years associated with additional costs. Similar results hold when we use the continuous measure of the Political Uncertainty Index by Baker et al. (2012). The uncertainty associated with gubernatorial elections, on the other hand, has no effect on the pricing of corporate bonds.